Information architectures: a framework for understanding socio-technical systems - Paul E. Smaldino; Adam Russell; Matthew R. Zefferman; Judith Donath; Jacob G. Foster; Douglas Guilbeault; Martin Hilbert; Elizabeth A. Hobson; Kristina Lerman; Helena Miton; Cody Moser; Jana Lasser; et al. (npj Complexity)
A sequence of technological inventions over several centuries has dramatically lowered the cost of producing and distributing information. Because societies ride on a substrate of information, these changes have profoundly impacted how we live, work, and interact. This paper explores the nature of information architectures (IAs)—the features that govern how information flows within human populations. IAs include physical and digital infrastructures, norms and institutions, and algorithmic technologies for filtering, producing, and disseminating information. IAs can reinforce societal biases and lead to prosocial outcomes as well as social ills. IAs have culturally evolved rapidly with human usage, creating new affordances and new problems for the dynamics of social interaction. We explore societal outcomes instigated by shifts in IAs and call for an enhanced understanding of the social implications of increasing IA complexity, the nature of competition among IAs, and the creation of mechanisms for the beneficial use of IAs.